EFEKTIVITAS GEL DAUN KIPAHIT (Tithonia diversifolia) TERHADAP PENYEMBUHAN LUKA DIABETES PADA TIKUS - Siti Khadijah; Astriani Natalia Br Ginting; Nerly Juli Pranita Simanjuntak (Jurnal Buana Farma, 2026)
Diabetes mellitus is a chronic disease commonly associated with complications such as diabetic wounds, which are characterized by impaired tissue perfusion, prolonged inflammation, and increased susceptibility to infection, resulting in delayed wound healing. Although various topical therapies have been developed, the use of herbal-based formulations for diabetic wound management remains an area of ongoing research. Leaves of Tithonia diversifolia are known to contain secondary metabolites such as flavonoids, tannins, alkaloids, and saponins, which may support the wound healing process. This study aimed to evaluate the effectiveness of Tithonia diversifolia leaf extract gel on wound healing in streptozotocin (STZ)-induced diabetic rats. This experimental study used 30 male white rats divided into six groups: normal control, negative control (gel base), positive control (octeniline gel), and treatment groups receiving Tithonia diversifolia extract gel at concentrations of 5%, 10%, and 15%. The extract was obtained by maceration using 70% ethanol and formulated into a topical gel. Wound length was observed on days 0, 3, 7, and 14, and the data were analyzed using One-Way ANOVA followed by Tukey HSD test. The results showed that Tithonia diversifolia extract gel significantly affected wound healing from day 3 to day 14 (p < 0.05). The 10% and 15% formulations demonstrated better wound healing than the negative control, while the 15% formulation showed the most optimal result, with a mean wound length of 0.40 mm on day 14. Therefore, Tithonia diversifolia extract gel has potential to be developed as a topical preparation supporting wound healing under diabetic conditions.